IPTEK PENCAPAIAN KINERJA DI DINAS KOMUNIKASI INFORMATIKA STATISTIK DAN PERSANDIAN DAERAH - Parera, Meyline Trisuksi; Manossoh, Hendrik (Universitas Sam Ratulangi, 2018)
This study aims to find out the factors that support the achievement of a performance in the SKPD, especially in Information Communication, Regional coding and statistics that have an important role in the scope of government in North Sulawesi. This study explains that the ability or skill factors and motivational factors have an important role in achieving an effective and efficient performance of employees and leaders based on their respective duties and functions.Keywords: Effective and efficient performance